ASAS-ASAS METODE PENDIDIKAN ISLAM - Nazwa, Aulia; Zahro, Fatimah (Proceeding International Seminar of Islamic Studies, 2024)
The many faults of teaching today are due to the lack of methods in teaching and are adversely affecting apprentice.Thus the study discusses the principle of the methods of islamic education.In the educational world this method is essential for a teacher in the teaching process.What methods of method in islamic education, and why there must be methods in the world of education.The purpose of this study is to know the methods of islamic education.This method of study is qualitative (library search)research that draws on a library,journal,book,and field research.After doing the study it can be known that islamic education methods are learning methods, teaching methods,educational methods,they can also facilitate and assist teachers in teaching process.